Recent Advances of Pyridinone in Medicinal Chemistry - Lin, Shibo; Liu, Chun; Zhao, Xiaotian; Han, Xiao; Li, Xuanhao; Ye, Yongqin; Li, Zheyu (Frontiers in Chemistry, 2022)
Pyridinones have been adopted as an important block in medicinal chemistry that could serve as hydrogen-bond donors and acceptors. With the help of feasible synthesis routes via established condensation reactions, the physicochemical properties of such a scaffold could be manipulated by adjustment of polarity, lipophilicity and hydrogen bonding, and eventually lead to its wide application in fragment-based drug design, biomolecular mimetics and kinase hinge-binding motifs. In addition, most pyridinone derivatives exhibit various biological activities ranging from antitumor, antimicrobial, anti-inflammatory, anticoagulant to cardiotonic effect. This review focuses on recent contributions of pyridinone cores to medicinal chemistry, and addresses the structural features and structure-activity relationships (SARs) of each drug-like molecule. These advancements contribute to an in-depth understanding of the potential of this biologically enriched scaffold and expedite the development of its new applications in drug discovery.